DIBRAST: A Computer-Aided Seismic Design Procedure for Frame Structures Equipped With Hysteretic Devices - Nuzzo, Iolanda; Ciliento, Francesca; Caterino, Nicola (Frontiers in Built Environment, 2020)
This paper describes a comprehensive computer-aided seismic design approach for both new and existing frame structures equipped with hysteretic dampers. As a matter of fact, despite continuous advancements in the state-of-art demonstrate the effectiveness of these devices in mitigating seismic hazard, nonlinearities involved in the problem and the articulated nature of most of the available design procedures often make them quite difficult to be implemented for real complex structures. To promote widespread use of hysteretic dampers, it is presented a thorough design approach which includes the application of a specific displacement-based design procedure by means of a computer-aided support tool, developed in Visual Basic environment and named DIBRAST. The software is realized to drive the designer through the dissipative system’s design. Required iterations are automated, thus significantly reducing time-processing. As final output, it delivers the damping braces mechanical properties in order to meet a specific performance objective. In order to further support practitioners in geometrical characterization of actual design dampers, authors developed an additional Visual Basic tool, Shear Link Non-Linear Model, able to provide yielding force and elastic stiffness of a specific type of hysteretic device according to its geometry and material. In addition, geometric details of each device can be preliminary determined by means of newly proposed design charts, herein presented, that allow to take into account buckling issue too. Both developed tools are freely available online. A case study is provided to demonstrate the effectiveness of the proposed design approach and tools.